THE EMPRISES OF LONGINGNESS ON BILLIE HOLIDAY’S “SOLITUDE” - Wijaya, Kusuma; Siadari, Yoshua Veron Handika Putra; Mulyanto , Luke Zefanezra; Margaretha, Sherlly; Pasopati, Rommel Utungga (Faculty of Letters Universitas Balikpapan, 2025)
Longing means craving for something, especially about love that has been gone for a long time. Solitude is a song by Billie Holiday released in 1952. The song describes the feelings of a singer who feels lonely because she has been left by her partner and also wants her partner to come back again. Then, this article would like to answer question of how may longingness be accentuated on Billie Holiday’s Solitude? The longing experience of connection and companionship is a key theme in the lyrics of the song. Billie Holiday employs how she artfully conveys the delicate balance between vulnerability and strength, intensifying the emotional impact of the song. In conclusion, the exploration of Solitude song and the emprises of longingness not only illuminates the profound emotional depths of her artistry, but also underscores the enduring power of music to express and to transcend the universal human experience of longing.